Intraoperative frozen section is essential for assessment of myometrial invasion but not for histologic grade confirmation in endometrial cancer: a ten-year experience - Ozturk, Ebru; Dikensoy, Ebru; Balat, Ozcan; Ugur, Mete Gurol; Aydin, Abdullah (Archives of gynecology and obstetrics, 2012)
Purpose To evaluate the accuracy of endometrial biopsy (EB), transvaginal ultrasonography (TVS) and intraoperative frozen section (FS) for assessment of myometrial invasion and histologic grade to predict more conservative surgery in endometrial carcinoma. Methods Demographic and clinical data of 220 patients with endometrial carcinoma were retrospectively reviewed. Preoperatively, the subjects were evaluated by EB and TVS. Intraoperatively, FS was also performed to evaluate histological grading and myometrial invasion. All patients underwent surgical–pathological staging after removal of the uterus, adnexa and pelvic lymph nodes. Sensitivity and specificity values were calculated for EB, TVS and FS with regard to detection of histological grading and neoplastic invasion of the myometrium according to the final histopathologic examination. Results Bilateral pelvic and common iliac lymphadenectomy was performed in 80 patients without performing intraoperative biopsy because of preoperative high risk. Evaluation of the tumor grade by preoperative EB showed a sensitivity, specificity and accuracy of 73, 97 and 91%, respectively. Evaluation of the tumor grade by intraoperative biopsy showed a sensitivity, specificity and accuracy of 73, 96 and 90%, respectively. Evaluation of the depth of myometrial invasion with TVS showed a sensitivity, specificity and accuracy of 52, 91 and 79%, respectively. Evaluation of the depth of myometrial invasion with intraoperative biopsy showed a sensitivity, specificity and accuracy of 86, 94 and 92%, respectively. Conclusions Evaluation of the histologic grade by EB and of the depth of myometrial invasion by intraoperative biopsy is a good option for deciding the necessity of lymphadenectomy.